(untitled) (De Legibus - Law Journal, 2026)
The judicialization of politics, characterized by the coincidental intervention of the Public Prosecutor’s Office in matters of a political nature, has called into question the balance of the system of checks and balances in contemporary democracies. We will analyze the role of the Public Prosecutor’s Office in mediating political conflicts, the limits of judicial activism and the impacts on judicial legitimacy. We argue that although courts play an essential role in protecting fundamental rights, excessive judicialization can erode the accountability of the democratic rule of law and politicize the judicial system, which can undermine trust in institutions. We conclude that it is necessary to carry out structural reforms at the institutional level that strengthen transparency and inter-institutional dialogue in order to ensure judicial legitimacy and democratic stability.